2016
DOI: 10.1002/app.43475
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun polymer of intrinsic microporosity fibers and their use in the adsorption of contaminants from a nonaqueous system

Abstract: The smooth and uniform polymer of intrinsic microporosity (PIM‐1) fibers, which have high adsorption capacities toward organic contaminants from nonaqueous systems, were successfully obtained by electrospinning. According to the N2 adsorption–desorption analysis, the surface area of the PIM‐1 fibers was higher than that of the PIM‐1 powder. The higher surface area of the fibers did not come from the interfiber pores but from intrafiber pores formed by the fast evaporation of the solvent in the electrospinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Zhang et al [33] was prepared PIM-1/ POSS fibrous membranes and they have investigated the ability of the membranes in oil-water separation. In addition, the adsorption of dyes from non-aqueous media by electrospun PIM-1 was reported by the same group [32]. However, the hydrophobicity limits the use of PIM-1 in aqueous solutions as it inhibits its interaction ability with waste molecules in water.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Zhang et al [33] was prepared PIM-1/ POSS fibrous membranes and they have investigated the ability of the membranes in oil-water separation. In addition, the adsorption of dyes from non-aqueous media by electrospun PIM-1 was reported by the same group [32]. However, the hydrophobicity limits the use of PIM-1 in aqueous solutions as it inhibits its interaction ability with waste molecules in water.…”
Section: Introductionmentioning
confidence: 94%
“…Electrospun fibers are employed in various applications such as filtration, biomedical, tissue engineering, nanocatalysis, sensors and food, etc. [24][25][26][27][28][29][30] On the other hand, electrospinning of PIM-1 is a relatively new concept which was investigated very recently [31][32][33][34]. Bonso et al [31] was successfully prepared electrospun PIM-1 fiber in tetrachloroethane solution which was then carbonized and used as an electrode for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the preparation of bead-free electrospun PIM-1 fibers by using 7 to 10% polymer in tetrachloroethane solutions with 127 and 292 kDa molecular weight of PIM-1 polymer [40][41][42]. In the present study, we have employed the PIM-1 with a molecular weight of 189 kDa (M w ) with a narrow PDI (1.78).…”
Section: Electrospinning Of Pim-1 Fibersmentioning
confidence: 99%
“…The fiber form can also be produced by electrospinning method which is fairly simple and versatile way to produce three-dimensional porous adsorbents for various applications [33][34][35][36][37][38][39]. Electrospinning of PIM-1 is a fairly new concept that was investigated recently [40][41][42][43]. Bonso et al [40] was first used tetrachloroethane solution to produce electrospun PIM-1 fiber mat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation